2011
DOI: 10.1063/1.3662096
|View full text |Cite
|
Sign up to set email alerts
|

Surface chemical modification for exceptional wear life of MEMS materials

Abstract: Micro-Electro-Mechanical-Systems (MEMS) are built at micro/nano-scales. At these scales, the interfacial forces are extremely strong. These forces adversely affect the smooth operation and cause wear resulting in the drastic reduction in wear life (useful operating lifetime) of actuator-based devices. In this paper, we present a surface chemical modification method that reduces friction and significantly extends the wear life of the two most popular MEMS structural materials namely, silicon and SU-8 polymer. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 20 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…Attachment of 1-aminoethanol to the surface of SU-8 would allow for hydroxyl groups to be reacted with S1 and for SU-8 to be a substrate for the surface-initiated cross-linking typical of CAP. 68 However, we were unable to modify any available surface epoxy groups using previously reported protocols, as any attempt in modifying the surface to −OH showed no change in water contact angle (Figure S12). Instead, we found that by using a very brief (3 s) reactive ion etch on the SU-8 surface, we could introduce the −OH terminal groups required to condense silanes onto the surface.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Attachment of 1-aminoethanol to the surface of SU-8 would allow for hydroxyl groups to be reacted with S1 and for SU-8 to be a substrate for the surface-initiated cross-linking typical of CAP. 68 However, we were unable to modify any available surface epoxy groups using previously reported protocols, as any attempt in modifying the surface to −OH showed no change in water contact angle (Figure S12). Instead, we found that by using a very brief (3 s) reactive ion etch on the SU-8 surface, we could introduce the −OH terminal groups required to condense silanes onto the surface.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…Microelectromechanical systems (MEMS) are devices with mechanical components whose characteristic size ranges from a few to a few hundred micrometers in size and that are directly integrated with electrical components. One of the key issues affecting the performance of such applications is the mechanical or electronic interactions between different parts on the MEMS device, either with or without contact, which respond to certain changes. For example, stiction is one of the greatest bottlenecks in the commercialization of highly complex MEMS systems. As a result, considerable research effort has been dedicated to surface modification techniques, where molecular films formed from various precursors are used to alter the surface properties and to meet application requirements, such as thermal stability. Thermal stability is essential for the practical application of MEMS devices, which are typically subjected to packaging processes and applications requiring long-term durability in specialized environments.…”
Section: Introductionmentioning
confidence: 99%
“…Dispersed PFPE droplets of micron to nanometer size range in SU-8 brought the coefficient of friction for pure SU-8 down from 0.82 to 0.03 at low load conditions. Surface modification techniques was proposed by Singh et al [15] for the reduction of the coefficient of friction and enhancement of wear life of SU-8. By the application of the above methods, tribological issues have been largely solved, however, this does not come together with an improvement in the mechanical properties such as the elastic modulus and hardness of the materials.…”
mentioning
confidence: 99%